Pemikiran Politik Islam di Indonesia (Natsir, Ba’asyir, Gus Dur,Dll) (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This article examines three major streams of Islamic political thought in Indonesia through a comparative analysis of the ideas of Mohammad Natsir, Abu Bakar Ba’asyir, and Abdurrahman Wahid (Gus Dur). Mohammad Natsir embodies the constitutional–integralist perspective, which seeks to formalize Islam as the foundation of the state by utilizing democratic mechanisms and constitutional political processes. In contrast, Abu Bakar Ba’asyir reflects a radical–ideological orientation that firmly rejects democracy and advocates the full implementation of Islamic Sharia through extra-constitutional and non-parliamentary movements. Meanwhile, Abdurrahman Wahid represents a substantive–cultural approach, opposing the formal institutionalization of Islam within the state while promoting Islamic values as ethical guidance for building a tolerant and pluralistic nation. The contrasting viewpoints of these three figures highlight the diversity of Islamic political discourse in Indonesia and illustrate the evolving interaction between religion and state. Overall, this study demonstrates how Islamic thought continues to adapt and remain relevant within Indonesia’s multicultural and democratic context.